73. N-acetyl-cysteine inhibits nociceptive pathway function. A combined animal and human study. Issue 1 (January 2015) - Piroso, S.; Di Stefano, G.; La Cesa, S.; Biasiotta, A.; Pasquale, E.; Leone, C.; Pepe, A.; Cruccu, G.; Nicoletti, F.; Truini, A.
<x xml:space="preserve">Abstract</x> Despite concerted efforts from pharmacologic research into pain, many patients fail to achieve sufficient pain relief with the currently available drug. N-acetyl-cysteine (NAC), an old and safe drug used as a mucolytic agent, enhances the endogenous activation of presynaptic metabotropic glutamate receptors type 2 and inhibits neurotransmitter release, thus possibly negatively modulating nociceptive pathway function. In this study we verified whether 1200 mg of oral NAC inhibits nociceptive pathway function by investigating how this drug modulates pain related responses in animals and humans. We have investigated the NAC-induced changes in tail flick evoked by heat stimulation in 6 mice; then in 10 healthy subjects we measured changes induced by NAC on thermal-pain perceptive thresholds as assessed by quantitative sensory testing and laser evoked potentials, according to a cross over, double-blind placebo-controlled design. In mice, NAC caused a tail flick delay, reverted by a single injection of the mGlu2/3 receptor antagonist (LY341495). In humans, NAC did not change the thermal-pain perceptive thresholds as assessed by quantitative sensory testing (P > 0.08), but reduced the laser pain ratings and the amplitude of laser evoked potentials (P < 0.05). Our data, showing that NAC delays the tail flick response and reduces the laser pain ratings and the amplitude of laser-evoked potentials, indicate that NAC inhibits nociceptive pathway function. These findings suggest that this drug is worthy of being tested in a clinical trial in patients with pain.